Toilet Training Readiness Scale for 0-5-Year-Old Children: A New Measurement Tool Based on a Child-Centred Approach - Adnan Barutçu; Burak Mete; Hakan Demirhindi; Saliha Barutçu; Aliye Kıdı; Nurdan Evliyaoğlu (MDPI AG, 2024)
Background and Objectives: There is no standardised approach to toilet training in children. This study aimed to determine the factors affecting the duration of toilet training in children aged 0-5 years and to develop a tool to assess the child's readiness to start toilet training. Materials and Methods: This cross-sectional study was conducted on 409 children aged 0-5 years. Social, economic, behavioural, and developmental characteristics that are effective in toilet training in healthy children were evaluated. A scale assessing children's readiness for toilet training (Toilet Training Readiness Scale-TTRS) was developed and content validated. Results: The mean age of the 409 children included in this study was 44.69 ± 13.07 months (min = 4; max = 60 months). The mean age of initiation of toilet training was 26.8 months. Most frequently, urine and faeces trainings were started together (52.1%). In the logistic regression analysis performed to evaluate the factors affecting the duration of toilet training, it was found that the TTRS score, mother's employment status, family type, child's first reaction, toilet type, and continuity of training were important predictors. The duration of toilet training showed a weak negative correlation with the scores obtained from the TTRS and the number of children in the family but a weak positive correlation with the age at the beginning of toilet training. The TTRS scores were inversely proportional to the duration of toilet training. Conclusions: Family characteristics, socioeconomic conditions, and readiness of the child for and no interruption in toilet training are important in completing toilet training in a short time and successfully. If a child-focused approach is adopted, evaluating the child from this point of view and initiating the training at the appropriate time may help to complete a more successful and shorter toilet training. We recommend that the scale we have developed be studied in other studies and different groups.